Role of the principal as perceived by teachers, principals, and district supervisors - Caoili, Eulogio M. 1917- (s.n.], 1968)
This study inquired on the administrative and supervisory roles of elementary school principals in selected elementary schools of the Baguio-Benguet Division as viewed by teachers, principals, and district supervisors. Results of the study may be used in the determination of in-service education programs for principals and other school administrators; and the enrichment of programs designed for the training of school administrators.